2022
DOI: 10.1038/s41467-022-32230-2
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-induced maternal microchimerism shapes neurodevelopment and behavior in mice

Abstract: Life-long brain function and mental health are critically determined by developmental processes occurring before birth. During mammalian pregnancy, maternal cells are transferred to the fetus. They are referred to as maternal microchimeric cells (MMc). Among other organs, MMc seed into the fetal brain, where their function is unknown. Here, we show that, in the offspring’s developing brain in mice, MMc express a unique signature of sensome markers, control microglia homeostasis and prevent excessive presynapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 80 publications
0
20
0
Order By: Relevance
“…These cells were subsequently gated based on H-2K b /H-2D b and H-2K d /H-2D d markers, with only H-2K b /H-2D bhi and CD45.2 hi cells being identified as MMc (Fig 4b). Intriguingly, we observed significantly fewer MMc in the brain compared to other tissues, which is a much smaller amount of MMc compared to those in the embryo brain (Fig 4c) 9 . Even though it is small, it contains immune cells including myeloid, B cells, and T cells (Fig 4d).…”
Section: Brain-specific Immune Cells Do Not Originate From Maternal S...mentioning
confidence: 64%
See 1 more Smart Citation
“…These cells were subsequently gated based on H-2K b /H-2D b and H-2K d /H-2D d markers, with only H-2K b /H-2D bhi and CD45.2 hi cells being identified as MMc (Fig 4b). Intriguingly, we observed significantly fewer MMc in the brain compared to other tissues, which is a much smaller amount of MMc compared to those in the embryo brain (Fig 4c) 9 . Even though it is small, it contains immune cells including myeloid, B cells, and T cells (Fig 4d).…”
Section: Brain-specific Immune Cells Do Not Originate From Maternal S...mentioning
confidence: 64%
“…Recent advances suggested that maternal microchimeric cells (MMc) convey health consequences for the offspring 9,[15][16][17] . The transfer of MMc from mother to fetus commences with maturing placentation, hence, with the onset of the second trimester in humans and around midgestation in mice 16 and shapes neurodevelopment and behavior in mice 9 . However, whether these cells remain in the brain for the entire life has not been evaluated yet.…”
Section: Brain-specific Immune Cells Do Not Originate From Maternal S...mentioning
confidence: 99%
“…One potential source of the WT IL2RA gene is maternal transfer. Maternal microchimerism, the transfer of cells from mother to fetus, is well established in humans and mice wherein maternal DNA/cells can persist for decades in offspring (24)(25)(26)(27)(28). Because IL-2Ra KO mice are infertile, they are generated by mating IL-2Ra heterozygotes; consequently, heterozygous maternal cells are likely present in IL-2Ra KO mice.…”
Section: Multiple Tissues In Il-2ra Ko Mice Have Low Levels Of the Il...mentioning
confidence: 99%
“…The low MMc murine model in utero showed a decrease in myeloid cells in the bone marrow with induced differentiation toward monocytes as well as the subdued maternal cell proportion resulting in increased severity and morbidity of murine cytomegalovirus (MCMV) infection in early life (Stelzer et al, 2021). In addition, postnatal depletion revealed that immune cells biased toward mature and activated profiles (Castellan & Irie, 2022), as well as hyperactivation of microglia in the brain (Schepanski et al, 2022). may affect the migration of MMc cells into the fetus.…”
Section: Additional Roles Of MMC Cells After Birthmentioning
confidence: 99%
“…These findings suggest that maternal cells have an immunological influence on their offspring, possibly orchestrating a tuned response to regulate neonatal reactivity. MMc cells observed in the brain (Aydın et al, 2018; Snethen et al, 2020) are suggested to play a role in neonatal promotion of homeostatic maintenance, neural communication, and behavioral performance in mice, with a reduction in MMc cells resulting in hyperactivation and disruption of function due to excessive refinement of microglia (Schepanski et al, 2022) (Figure 4). As all biological processes are susceptible to errors and as MMc elicits an alloimmune response (Bracamonte‐Baran & Burlingham, 2015), it is possible that this influence could seldom stray from a beneficial role to a detrimental one in progeny.…”
Section: Additional Roles Of MMC Cells After Birthmentioning
confidence: 99%